MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN MELALUI MOTIVASI DAN KINERJA GURU DI SMK - Eko Purnomo (Jurnal Ilmu dan Budaya, 2019)
Significant contributing factor to the quality of education include teachers' motivation and performance. Motivation and teacher performance, will support the achievement of quality education. This research is quantitative. Data were collected by questionnaire, observation, and documentation. This study uses census approach, which is taking the data of the whole unit of observation. Data analysis method used is descriptive percentage, regresion, and t test. Based on this research, it was found that: 1) the work motivation of teachers teacher performance in the excellent category, and the quality of education in the excellent category, significa nt influence motivation work to teachers performance; 3) There is significant influence motivation to work on educational quality  4) No significant effect oneducational quality teacher performance a significant effect the performance of teachers to the quality of education, 5) there is a significant influence job motivation of teachers and teacher performance together on educational quality). The results of this study reinforce the theory by Bemandin Joice and Keith Davis that the quality of education is influenced by the knowledge, skills, abilities, attitudes, and behavior, motivation, and performance of the personal organization.